A New Species of Cyclobulura (Nematoda: Subuluridae) from Zaedyus pichiy and Chaetophractus vellerosus (Xenarthra: Dasypodidae) in Argentina - Navone, Graciela Teresa (2010)
Cyclobulura superinae n. sp. collected from Zaedyus pichiy and Chaetophractus vellerosus is herein described as the second species in Cyclobulura Quentin, 1977, and the first subulurid in armadillos. The species is unique in the spur-like structures present at the tip of both spicules, yet they conform to the description of Cyclobulura in the structure of the buccal parts. Specimens of the new species show longer chordal lobes and more conspicuous radial lobes and are smaller than specimens of C. lainsoni. In addition, males of C. superinae exhibit a spur-like process in the distal end of the spicules and a shorter tail (170 vs. 300 mm) with no spine. Finally, the eggs of C. superinae are smaller (60–89 3 45–71 vs. 95–100 3 80–85). To our knowledge, the new species is the first subulurid nematode found in an armadillo.